Biogeographic evaluation of the dragonflies and damselflies in the Eastern Iberian Peninsula - L. Fontana-Bria; E. Frago; E. Prieto-Lillo; J. Selfa (Arxius de Miscel-lània Zoològica)
Insects are one of the most diverse groups of animals in terrestrial ecosystems, and are thus a good model system to study macrogeographic patterns in species’ distributions. Here we perform a biogeographical analysis of the dragonflies and damselflies in the Valencian Country (Eastern Iberian Peninsula). We also compare the species present in this territory with those in the adjacent territories of Catalonia and Aragon, and with those present in the whole Iberian Peninsula. Furthermore, we update the list of species of dragonflies and damselflies in the Valencian territory (65 species), and discuss the current status of two of them: Macromia splendens and Lindenia tetraphylla. Our results highlight that the Valencian Country has a higher proportion of Ethiopian elements but a lower proportion of Eurosiberian elements than Catalonia and Aragon. We also emphasize the importance of volunteer work in providing new knowledge on this group of iconic insects, and the relevance of museum collections in preserving them. The role of climate change in the distribution of Odonata is also discussed.